An unusual cure for acromegaly. (7th September 2012) - Kohler, Sibylle; Tschopp, Oliver; Bernays, René Ludwig; Schmid, Christoph
Abstract : The authors present the case of a 30-year-old female patient with acromegaly whose disease had not been cured after transcranial neurosurgery, two transsphenoidal surgeries and stereotactic radiosurgery. She required treatment with octreotide and pegvisomant to normalise growth hormone levels. Seven years after the diagnosis of acromegaly, she noticed acute vision loss in her left eye and presented with meningism. She had an intrasellar abscess which was confirmed and treated by surgical drainage. As a result of the abscess, she was cured of acromegaly and able to discontinue both octreotide and pegvisomant.